Direct dissolution of UO2 in carboxyl-functionalized ionic liquids in the presence or absence of Fe-containing ionic liquids. Issue 42 (19th October 2020) - Yao, Aining; Xiong, Xiaogen; Kang, Mingliang; Guo, Yanan; Chen, Chong; Chu, Taiwei
Abstract : Direct dissolution of UO2 in carboxyl-functionalized ionic liquids was achieved, and the addition of Fe-containing ionic liquids would improve the dissolution kinetics. Abstract : Dissolution of UO2 is a prerequisite for the reprocessing of spent nuclear fuel. This study showed that UO2 could be directly dissolved in a single carboxyl-functionalized ionic liquid (IL), [HOOCMmim][Tf2 N] 1-carboxymethyl-3-methylimidazolium bistriflimide, or [HOOCEtmim][Tf2 N] 1-carboxyethyl-3-methylimidazolium bistriflimide. The addition of an extra Fe-containing IL, [Emim][FeCl4 ] (Emim, 1-ethyl-3-methylimidazolium) or [Bmim][FeCl4 ] (Bmim, 1-butyl-3-methylimidazolium) could significantly improve the dissolution kinetics. Results demonstrated that the dissolution process in the early stage could be described by using the pseudo first-order rate law. The apparent activation energy for UO2 dissolution in the mixture of the Fe-containing IL and carboxyl-functionalized IL was calculated to be ∼67 kJ mol −1, implying that the reaction was mainly controlled by a chemical process. Nevertheless, the influence of the diffusion process is non-negligible since the IL has a relatively high viscosity that can retard the diffusion of the formed uranyl species from the UO2 surface. Spectroscopic studies and density functional theory calculations indicated that the uranyl ion coordinated with carboxylate groups is the predominant product for UO2 dissolution in the single carboxyl-functionalized IL, while uranyl chloride complexes would also form in the mixed ILs. The dissolved uranyl species can be successfully recovered from the ILs by extraction. The success of UO2 dissolution in the carboxyl-functionalized IL with or without the Fe-containing IL indicates that the Fe-containing IL and oxygen can serve as an effective catalyst and oxidant for the dissolution of UO2, respectively.